The Effect Of Packaging Design Elements On Youth Purchase Intention Of Junk Food - Puteri Nur Amira Abdl Rahman; Rabitah Harun; Nur Rashidi Johari (Universitas Muhammadiyah Sidoarjo, 2020)
This research provides new knowledge on the purchase intention towards junk foods. The main purpose of this research study is to examine the packaging design elements as a determinant factor to purchase junk food among youth consumer that might be one of the most essential variable in marketing field. One of the aims of this study is covering the shortcomings of previous studies that didn't observe main factors that influence the consumer purchase intention toward junk food. The various packaging elements (packaging colour, packaging graphic, packaging size, packaging material and packaging label) have been conceptualized into integrated frameworks to investigate the factors that influence consumer purchase intention toward junk food products amongst youth. Data were collected from sample size of 322 respondents mainly degree students from the faculty of Hotel Management and Tourism, and Faculty of Engineering in Universiti Teknologi MARA, Penang. This study is further validated through a survey method used of questionnaire distribution. The data were further process and analyse using Statistical Package for Social Sciences (SPSS) version 22.0. The findings revealed that only four elements which are packaging colour, packaging graphic, packaging size and packaging label are positively significant with consumer purchase intention toward junk food while the packaging material was not significant with the consumer purchase intention toward junk food.